2001
DOI: 10.1115/1.1421049
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Microstructural Evolution During Large Strain Cold Working of Metals by Means of Synchrotron Radiation—A Comparative Overview

Abstract: Dislocation densities, arrangements and long range internal stresses in cold rolled polycrystalline Cu, Ni, and Al, as well as in cold torsioned Fe, were determined by X-ray diffraction profile analysis using synchrotron radiation. At different deformation degrees, scanning measurements across single grains with a focal spot of less than 50 μm were carried out, in order to inform on the features of the deformation induced substructure. At small deformations including stage III, the dislocation densities and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Such behaviour was observed using in situ deformation in synchrotron radiation experiments. The cell walls were shown to change their structure from polarised dipole walls to polarised tilt walls, which allows storing of a higher dislocation density (Zehetbauer et al, 2002). It is also possible that part of those dislocations residing in the cell interiors is accommodated in the walls, which explains the decrease and increase of the respective dislocation densities under ECAP straining up to 12 passes.…”
Section: Article In Pressmentioning
confidence: 99%
“…Such behaviour was observed using in situ deformation in synchrotron radiation experiments. The cell walls were shown to change their structure from polarised dipole walls to polarised tilt walls, which allows storing of a higher dislocation density (Zehetbauer et al, 2002). It is also possible that part of those dislocations residing in the cell interiors is accommodated in the walls, which explains the decrease and increase of the respective dislocation densities under ECAP straining up to 12 passes.…”
Section: Article In Pressmentioning
confidence: 99%
“…[22] It is suggested that these processes occur simultaneously along with the increase in misorientation angle among subgrains, which is again part of the recovery mechanism involving dislocations in the cell wall, which rearrange themselves in order to screen the long-range stress field. [11,46] While the observation of 1-to 4-lm large grain aggregates (Figure 4) after N = 16 does not significantly change the mean grain size value due to the small number of such large grains, a non-negligible volume fraction may influence the final mechanical properties. Indeed, the lower YS measured in N = 8, 12, and 16 specimens may be also explained by the presence of such recovered deformation substructures.…”
Section: A Grain Size Measurementsmentioning
confidence: 99%
“…In contrast to these observations, XRD peak broadening analysis has led to a description of the microstructure [9,10,11] based on the coherent scattering of domains. Because no coherency results from X-rays scattered from different cells, the microstructural features with the shortest average spacing between misorientations are measured.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the dislocation density in the cell walls should lead to some qualitative changes in the structure of the lattice . M. Zehetbauer and others [18] made a supposition about a gradual transformation of dipole walls into tilted ones. The process is accompanied by an increase of misorientations between neighbouring cells (Fig.…”
mentioning
confidence: 99%